Teaching methodologies in communication design - Rijo, Cátia (2019)
This paper aims to contribute for the discussion in design teaching and its consequent research context, in design research and teaching. It is intended to discuss the importance of reflecting and analyzing the modus operandi usually adopted and the results obtained by adopting a design process methodology in the educational field, particularly in Communication Design Education. Therefore, our main goal is to implement and propose a methodology centered and driven by practical action, as much as possible in a real context scenario, structured according to the different phases of a design project. Signed in collaborative processes, the action developed it is characterized by the interdisciplinary dialogue in formal, informal, generational and culturally plural contexts able to characterize and test and evaluate the approach to different thematic, enabling to enriches and optimize the design experience as the process of apprehension.